Measuring success in PPP road projects in Europe: A performance measurement system (PMS). - Liyanage, Champika; Villalba-Romero, Felix; Njuangang, Stanley (Routledge, 2016)
There are many studies carried out that aim to search for the most appropriate approach to conceptualise and measure the success of Public Private Partnership (PPP) projects in infrastructure. The concept of a project success is commonly referred to in the academic literature as broad criteria including diverse Critical Success Factors (CSFs), and the way to measure the criteria usually includes diverse elements known as Key Performance Indicators (KPIs). Although analysis of success could vary according to the type of sector and class of project, there is no clear consensus about the method of measuring the success of projects using KPIs. The main purpose of this chapter is to fill this gap by presenting a robust assessment of the success of PPP. This assessment is presented as a Performance Measurement System (PMS) and the PMS is tested using 13 selected case studies. The selected case studies have been taken from the case database of the P3T3 COST TU1001 action Public Private Partnership in Transport: Trend and Theory networking project.
http://biblioteca.cchs.csic.es/registro_buscareditoriales.php?id=770 https://www.routledge.com/our-products/open-access-books/publishing-oa-books/chapters?srsltid=AfmBOopyu-ha7fTRrj4k9_simE8Qc3gpFlv1W2YeK_3xgPVAeyC3EcA3
Keywords: Cooperación sector público-privado; Roads; Performance measurement system; Key performance indicators; Public private partnerships